Antibacterial Activity and Proposed Mode of Action of Extracts from Selected Zimbabwean Medicinal Plants against Acinetobacter baumannii - Auxillia Machingauta; Stanley Mukanganyama (Wiley, 2024)
Acinetobacter baumannii was identified by the WHO as a priority pathogen in which the research and development of new antibiotics is urgently needed. Plant phytochemicals have potential as sources of new antimicrobials. The objective of the study was to determine the antibacterial activity of extracts of selected Zimbabwean medicinal plants against A. baumannii and determine their possible mode of action. Extracts were prepared from the leaves of the eight plants including the bark of Erythrina abyssinica using solvents of different polarities. Antibacterial activity was evaluated using the microbroth dilution method coupled with the in vitro iodonitrotetrazolium colorimetric assay. The effect of the extracts on membrane integrity was determined by quantifying the amount of protein and nucleic acid leaked from the cells after exposure to the extracts. The effects of the extracts on biofilms were investigated. Toxicity studies were carried out using sheep erythrocytes and murine peritoneal cells. Seven out of eight evaluated plant extracts were found to have antibacterial activity. The Combretum apiculatum acetonie (CAA) extract showed the highest inhibitory activity against A. baumannii with a minimal inhibitory concentration of 125 µg/mL. The minimum inhibitory concentration (MIC) of the CAA extract caused a protein leakage of 32 µg/mL from A. baumannii. The Combretum apiculatum acetonie (CAA), C. apiculatum methanolic (CAM), Combretum zeyheri methanolic (CZM), and Erythrina abyssinica methanolic (EAM) extracts inhibited A. baumannii biofilm formation. The EAM extract was shown to disrupt mature biofilms. The potent extracts were nontoxic to sheep erythrocytes and mouse peritoneal cells. The activities shown by the extracts indicate that the plants have potential as sources of effective antibacterial and antibiofilm formation agents against A. baumannii.